Control of Pollutants in Crude Oil through Processing Oil Well Injection Water by Physical Methods: An Experimental Investigation - Potrous, Saad M. (Techniques and Innovation in Engineering Research Vol. 4, 2022)
In this research, two types of additives were used to the injection water (A and B) with three different concentrations for each type to a fixed volume of injection water. Laboratory experiments were carried out in the Department of Petroleum Engineering, College of Engineering, University of Basra. The viscosity of the waters after adding these materials was calculated and compared with the viscosity of a sample of crude oil taken from Zubair-2 field in Basra Governorate, which feeds the South Refineries Company with Zubair-1 field for the purposes of crude oil refining operations. Three samples were used for research purposes (A1, A2, A3) and (B1, B2, B3) with weights 3, 6, 18gm for each sample added to a fixed volume of injection water of 60ml. The results showed that the total dissolved salts (T.D.S) is 92ppm for injection water before addition and 117, 146, 140ppm for samples A1, A2, A3 respectively and 467, 546, 710ppm for samples B1, B2, B3 respectively after addition. The viscosity of Zubair-2 crude oil was measured, which is 7.72 mm2/s, compared to injection water, which is 2.73 mm2/s. The viscosity of samples A1, A2, A3 are 3.98, 5.925, 9.42 mm2/s, respectively, while the viscosity of samples B1, B2, B3 were not recorded, due to the inability of the viscometer to measure. For the purpose of measuring the height of the oil-crude mixture with the injection water, samples A!, A2, A3 were added with additives with weights 9, 18, 54 gm, respectively, to a fixed volume of injection water for all samples by 80ml, where the heights of the mixture reached 10.6, 10.8, 11.5 cm respectively. The results of this research confirmed a complete isolation between the surface of the crude oil with the injection waters with an increase in the crude oil’s rise as the concentration of the additive increased, and this means an increase in the production of the oil field while the salinity of the water remained not exceeding 146 ppm as a maximum, as the viscosity factor was used in the injection water to raise the level Crude oil is rather the density when used to raise it. Which achieves control of pollutants in crude oil, especially organic and inorganic chlorides, which affect the economic aspect of the oil produced, in addition to the occurrence of technical problems that lead to damage to the refining equipment of crude oil refineries companies.